Analisis Faktor-Faktor Yang Berpengaruh Pada Loyalitas Pelanggan Klinik Saraf Rumah Sakit Jiwa Daerah Dr Rm Soedjarwadi - Rima Hayu Sri Widadi; Muhammad Farid Wajdi; Ahmad Mardalis (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2015)
The Customer loyalty is absolutely necessary in this era of increasingly fierce competition, including in the health care business. Because of the absence of customer loyalty, the hospital will not grow well even be left by customers. The purpose of this study was to analyze the factors that affect customer loyalty in Clinical of Neurology RSJD Dr. RM Soedjarwadi. The total sample of 139 respondents in there with purposive sampling. Based on SEM analysis concluded that the impact of service quality on customer satisfaction. Service quality effect on patient or customef. The hospital image effect on patient or customer satisfaction. The hospital image effect on patient or customer loyalty. Patient satisfaction effect on patient or client. And the good service quality , the image of the hospital and the patient or the customer satisfaction significant effect on customer loyalty simultaneously in Clinical of Neurology RSJD Dr. RM Soedjarwadi. While based on the acquisition value of the direct effects and indirect effects of customer satisfaction can be inferred intervening variable for the relationship between service quality and customer loyalty, while for the relationship between the image of the hospital with customer loyalty cannot be termed as intermediate variable (intervening).